2018
DOI: 10.1016/j.jceh.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Encephalopathy and Astrocyte Senescence

Abstract: Hepatic Encephalopathy (HE) is a severe complication of acute or chronic liver diseases with a broad spectrum of neurological symptoms including motor disturbances and cognitive impairment of different severity. Contrary to former beliefs, a growing number of studies suggest that cognitive impairment may not fully reverse after an acute episode of overt HE in patients with liver cirrhosis. The reasons for persistent cognitive impairment in HE are currently unknown but recent observations raise the possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…Hepatic encephalopathy is a common complication occurring upon severe liver dysfunction. Albeit it is largely accepted that hyperammonemia-induced impairment of astrocyte function plays a major role in mediating neurological disturbances (Görg et al, 2018; Häussinger and Görg, 2010; Norenberg, 1987), the underlying molecular mechanisms are not well understood and numerous models were proposed (Cash et al, 2010; Cordoba, 2014; Ott and Vilstrup, 2014). One particular aspect that is quite controversially discussed is the role of altered brain energy metabolism caused by hyperammonemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic encephalopathy is a common complication occurring upon severe liver dysfunction. Albeit it is largely accepted that hyperammonemia-induced impairment of astrocyte function plays a major role in mediating neurological disturbances (Görg et al, 2018; Häussinger and Görg, 2010; Norenberg, 1987), the underlying molecular mechanisms are not well understood and numerous models were proposed (Cash et al, 2010; Cordoba, 2014; Ott and Vilstrup, 2014). One particular aspect that is quite controversially discussed is the role of altered brain energy metabolism caused by hyperammonemia.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of free radicals can lead to mitochondrial dysfunction, energy failure as well as formation of the mitochondrial transition pore (Albrecht and Norenberg, 2006; Bai et al, 2001, 2001; Frank et al, 2012; Stewart et al, 2000) or RNA oxidation (Görg et al, 2008). Several studies demonstrated that hyperammonemia primarily disturbs astrocyte function resulting in subsequent neurological dysfunction (Görg et al, 2018; Häussinger and Görg, 2010; Norenberg, 1987). Astrocytes have an essential role to ensure neuronal function, such as provision with nutrients and recycling of the neurotransmitter glutamate (Sontheimer, 1995; Zalc, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress results from inefficient removal of reactive oxygen species (ROS) and free radicals from astrocytes, leading to major damage of cells and finally cell death [22]. Oxidative stress is directly related to malfunction of astrocytes, which is responsible for deterioration in cognitive performance of patients with cirrhosis and HE [23].…”
Section: Pathophysiology Of Hepatic Encephalopathymentioning
confidence: 99%
“…In addition, blood-brain barrier (BBB) permeability/function, cerebrospinal fluid composition, glymphatic flow, cerebral energy metabolism, neurotransmission and cell-cell communication are all deranged, causing neurological impairment and providing potential therapeutic targets. [11][12][13][14][15][16][17] The AASLD-EASL clinical guidelines for HE, published in 2014, were an important initiative. 1 However, since this publication, there have been many advances in the classification of HE, as well as our understanding of its pathophysiology, diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%